THE GROWING ROLE OF FINANCIAL TECHNOLOGIES IN THE CONTEXT OF DIGITAL ECONOMY DEVELOPMENT - RIABOKIN, M.; KOTUKH, Y. (Herald of Kyiv Institute of Business and Technology, 2024)
The article delves into contemporary global trends in financial technology (fintech) development within the framework of the burgeoning digital economy. It scrutinizes the net income generated by fintech enterprises across various regions, juxtaposed with the economic development levels of countries worldwide. Furthermore, prognostic indicators for transaction volumes and the proliferation of fintech market users across distinct segments are delineated until the year 2028. In addition, the article scrutinizes pertinent sectors of fintech industry advancement projected over the ensuing five years on a global scale, with specific attention given to the landscape in Ukraine. A comprehensive analysis of the present state of fintech market evolution in Ukraine ensues, encompassing intricate facets such as the distinctive attributes of payment services and banking operations amid the enactment of the Law of Ukraine "On Payment Services," alongside endeavors towards the adoption of open banking principles. Moreover, the discourse encompasses the prospects for the National Bank of Ukraine’s initiation of an E-hryvnia, alongside the attendant challenges pertinent to fortifying cybersecurity within the financial domain. Drawing from the research findings, an exhaustive exploration of the merits and demerits inherent in fintech solutions and products is conducted.